"Abortion? That's for Women!" Narratives and Experiences of Commercial Motorbike Riders South-Western Uganda - Nyanzi, Stella; Nyanzi, Barbara; Kalina, Bessie (African journal of reproductive health, 2005)
Although constitutionally illegal, induced abortion is a vital reproductive health option in Uganda. analyses men's narratives about meanings of, and experiences with, abortion. Men play significant tion as instigators, facilitators, collaborators, transporters, advisors, informers, supporters or punishment Many participants were knowledgeable about abortion. Attitudes were ambivalent, with initial reactions and relegation of abortion to women's private domains. Further exploration, however, revealed active and involvement of men. Interpretations of abortion ranged from 'dependable saviour' to 'deceptive Though a private action, abortion is socially scripted and often collectively determined by wider social kinsmen, the community, peers, law and religion. A disjuncture exists between dominant public health and the reality of local men who interact with women and girls as wives, lovers, sex sellers, mothers, sisters. Interventions targeting men about abortion should include safe sex education, provide services and create stronger social support mechanisms. Policy and law should incorporate local knowledge practice
Keywords: Abortion; Attitude; Perception; Support